Variety of fishes for sale - Mumbai Archive Project Team (Jio Institute, 2024)
Before they are sold, fish are thoroughly cleaned and gutted to remove undesirable parts like fins, tails, bones, scales, and viscera. Instead of being discarded, fish waste is processed to produce fishmeal and fish oil, both of which have numerous industrial and agricultural applications. Fishmeal is a valuable source of protein and nutrients used in animal feeds for livestock, poultry, and aquaculture.